1993
DOI: 10.1002/jcp.1041570215
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐like molecules bind differentially to prion‐proteins and change their intracellular metabolic fate

Abstract: PrPSc is the only known component of the scrapie prion. The difference between PrPSc and its normal isoform PrPc is probably conformational, since no difference has been found in the amino acid sequence or postranslational modifications between both proteins. Heparan sulfate (HS) has been shown to be a component of amyloid plaques in a number of diseases including the prion diseases. We now present evidence that PrP can specifically bind to heparin-like compounds and that this interaction might have a physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 28 publications
4
120
0
Order By: Relevance
“…Such strain-specific factors could include an as yet unidentified scrapie-specific nucleic acid as well as other protein and nonprotein components that may be closely associated with PrPres (33)(34)(35)(36)(37)(38). Strain specificity might also be encoded by the conformation of the PrP-res molecule (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…Such strain-specific factors could include an as yet unidentified scrapie-specific nucleic acid as well as other protein and nonprotein components that may be closely associated with PrPres (33)(34)(35)(36)(37)(38). Strain specificity might also be encoded by the conformation of the PrP-res molecule (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…First, HS accumulates in cerebral prion amyloid plaques (20) and it also associates with the more diffuse PrP Sc deposits that appear in early stages of prion diseases (21). Second, a variety of sulfated glycans, such as low molecular weight heparin (22), suramin (23), pentosan polysulfate, and dextran sulfate (23)(24)(25), and dextran-based HS analogs reduce the formation of PrP Sc in infected cells and in some cases prolong the incubation time of experimental prion diseases. Because PrP binds heparin (22,26,27), it has been suggested that sulfated glycans exert their anti-prion effects by competing with the binding of PrP C to putative cellular pro-prion GAGs (22).…”
mentioning
confidence: 99%
“…A number of studies are consistent with the involvement of heparan sulphates in the biogenesis of prions. A variety of sulphated glycans, including pentosan polysulphate [13,28], dextran sulphate 500 [8,12,28], heparin [49], and various heparan mimicking molecules [1,126] are potent inhibitors of PrP Sc accumulation in several cell lines infected with murine prions and in Rov cells infected with a sheep scrapie agent [98], presumably by competitive inhibition of cellular heparan sulphates for the binding to PrP C [49]. More direct evidence for a role of cellular heparan sulphates in the formation of abnormal PrP was obtained by showing that treatment of infected N2a cells with heparinase III resulted in a marked reduction of PrP res [11].…”
Section: Cell Models Propagating Naturally-occurring Prion Isolatesmentioning
confidence: 99%
“…The underlying mechanisms have not been determined. Since heparan sulphates can bind numerous molecules, including PrP C [29,49,149], one possibility is that the heparan sulphate moieties of proteoglycans could help bring together partners critically involved in the conversion process, such as PrP C , PrP Sc , and other possible cofactors. Inhibition of the expression (either by antisense RNA and siRNA) or function (by antibodies) of the 37 kDa/67 kDa laminin receptor (LRP/LR) prevents PrP res accumulation in infected N2a and GT1 cells [78].…”
Section: Cell Models Propagating Naturally-occurring Prion Isolatesmentioning
confidence: 99%